The «cuencana» experience as a «rite of passage» for Spanish academic migration to Ecuador - Pérez-Gañán, María del Rocío; Rodríguez-Fariñas, María Jara (Iberoamerican Journal of Development Studies, 2023)
The socio-economic crisis Spain has experienced since 2008, connected with the process of the Ecuadorian government to attract qualified human resources abroad, both converged in a massive insertion of Spaniards in as researchers and professors at universities in Ecuador during the period 2011-2015. Within the framework of a global knowledge economy that generates asymmetric processes of concentration, expulsion and instrumentalization of human potential, this study attempts to understand, through a biographical method (analysis of the seven stories of migration of Spanish academics), the mechanisms activated in the dynamics of North-South academic mobility, in these processes of qualified labor migration, expelled in a search for professional advancement, to later access an academic career in the country of origin.